Millenial Generation Financial Management Application Using Kakeibo Method Android- Based - Lombok, Rizky Dwi Putra Sani; Sentinuwo, Steven R.; Paturusi, Sary D. E. (Jurnal Teknik Informatika, 2021)
Every financial activity or financial management, both income and expenses, always occurs at any time. Each individual also has an income or expense that varies according to profession, age, status, place of residence, and gender. All of these factors can cause differences in expenses and income that are different for each individual, including the millennial generation. According to Forbes, millennials spend more of their money on things like shopping, fuel, restaurants, cellphones (data packages), hobbies, electronics, and fashion (clothes). This shows how the millennial generation spends their money based on their will (will) and not their needs (needs) so that it can be seen that some of the millennial generation still do not understand how to manage finances properly and correctly, this is the reason for this research, on how to provide information to the millennials about how to properly manage finances and how this information can be managed and useful for millennials. So that the purpose of this research is to create an android-based application by applying the kakeibo method, which is a method for managing finances. This application was developed using the Rapid Application Development (RAD) method and based on Android. This application can help millennials in managing finances using the kakeibo method.